Subprime Crisis – A Corporate Acquisition Opportunity? - VISHAL SRIVASTAVA; SUNDER RAM KORIVI; DIPASHA SHARMA (STIE Malangkucecwara, 2021)
Corporate acquisition can be considered as one of the best processes of corporate restructuring. This study is focused to evaluate the post-acquisition operating performance of listed Indian companies (acquirers) which have made acquisitions during subprime crisis period i.e. from FY 2007-08 to FY 2009-10. Paired sample t-test has been used on four operating performance indicators i.e. Return on Equity(ROE), Return on Assets (ROA), Operating Profit margin (OPM) and Operating Cash flow to Net Sales ratio (OCF/Net Sales) to check whether operating performance of acquirers has significantly improved post-acquisition. This study has revealed that there is no significant improvement in firms’ operating performance based on financial parameters i.e. Return on Equity (ROE), Return on Assets (ROA) and Operating Profit Margin (OPM), post corporate acquisitions made during subprime crisis period. The study finds that there was negative impact based on these parameters. Though Operating Cash Flow to Net Sales ratio has improved significantly for the companies which have made acquisition in FY 2007-08 and FY 2008-09 but similar findings could not be achieved for FY 2009-10. This study will find its significance in present scenario wherein corporate acquisitions are seen as the fastest way to achieve growth. Corporate world may derive its growth strategy from this study.